Identifying ESP Course Materials for Students of Magister Management: A Needs Analysis - Nirwanto Maruf; Eva Desembrianita; Dahlia Husain Husain (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
English for Specific Purposes (ESP) is an approach in teaching English that is relevant with the students’ field of study, it is made specifically for students’ learning and language use including its objective and content This study aims to explore the target and learning needs of students in Magister Program of Management (MM) by employing need analysis method. A descriptive analysis using a quantitative approach with forty-eight students of the Magister Program of Management (MM), which consist of 37 males and 10 females. The study results illustrated that the awareness of the need of target and learning needs will determine what is considered as acceptable and reasonable contents in the language courses. These acceptable and reasonable contents have to be the basis in designing ESP., material course, since students’ needs will determine the learning outcomes, and will be useful for their future jobs.